Gravity data processing of field camp geophysics in Karangsambung (2005-2019) - Wahyudi, E J; Laesanpura, A; Aji, W (Journal of physics. Conference series, 2022)
Gravity data was collected from a previous survey in Karangsambung 2005-2019 (before the restriction of field camp activities due to the Covid-19 pandemic). Luk-Ulo Mélange Complex in the Karangsambung area has been the subject of local and regional studies for geoscience students due to the interesting exposure of outcrops that have been interpreted as product of subduction (the Indo-Australian plate under the Eurasian plate in the Late Cretaceous to Early Paleocene time). The data for this gravimetric study based on 2592 observations over an area of inside (9.1 × 9.1) square kilometers. The gravity data were observed by students in the field camps for several years and then we compile. In this work we present simple data processing and simple calculation for modeling. The Bouguer anomaly map was processed using a density estimate of 2.31 g/cc for slab-Bouguer and terrain correction/reduction. The residual anomaly map was obtained by simple calculation of trend surface analysis (second order polynomial order). The inverse model was calculated using a simple algorithm for 2.5D and the program was built by accomodate topographic variations in the study area. Slice sections (SW-NE) of residual anomalies with a length of more than 8 km were inverted to obtain the contrast density distribution as a subsurface model. The subsurface images can then be analyzed and correlated with geological surface maps in the study area. The work in this paper is mainly presented as an ilustration of simple data processing and inverse modeling, so that the outcomes of this work are: (1) Bouguer anomaly map, (2) residual anomaly map, and (3) contrast density distribution as SW-NE section in the Karangsambung area. The value of the Bouguer anomaly map from this study is in the range of 88 to 112 mGal, and the value of the residual anomaly map is in the range of -12 to 10 mGal. The contrast density distribution from the inverse model in this study is in the range of -0.3 to 0.6 g/cc.